MELANGKAH KE DALAM DUNIA MISTIKNYA WILIAM JAMES - Maurenis, Andreas (LOGOS, 2016)
Mystical experience has become a new discourse and has been resounded in the midst of our world which has lost the feel of its religiosity due to modernism and secularism. Though modernism gives advance in human life but it is undeniable that somehow it affects to the very core of human thirst for a deepest spiritual growth and improvment. So, in this part William James has become one of the most known philosophers in nineteen century and in the same time as a psychologist who tries to bring back the mystcal experience as a vessel for every individual to find the true meaning of their spirituality need. James is going to re-present this encountered-experience with the transcendent reality into the midst of human being’s world day to day. By deepest reflection of knowledge, James tries to understand the mystical experience by giving the comparison of mystical experience with some psychology aspect. In other hand, he favors to let people know how the rasionalism deals with this kind of spiritual encounters. And he explains too, how the mystical experience comes to human’s life. Further, James also gives the understanding of mysticalexperience as far as it useful for the personal growth and the growth of social relationship in human being’s life.